Precise Control of Dynamic Object by Combining of the Advantages of Different Sensors - Zhmud, Vadim; Yadrishnikov, Oleg; Semibalamut, Vladimir (Journal of Advances in Management Sciences & Information Systems, 2015)
Precise control of dynamic objects with negative feedback loop is widely used in science and industry [1-3]. Control accuracy depends on properties of the regulator, as well as on the accuracy of the sensor of the output value. Often the choice of the best sensor is impossible, because the different sensors may have different, and none of them is the best over the whole frequency range. In this paper, the research work is carried out in the base of the mathematical simulation and some theory. The modeling proof of the method effectiveness is carried out on specific examples. The sensors together with the object give the task with single input and two outputs (SITO).